Redressing Security and Crime in Nigeria through Traditional Yoruba Social Values and Cultural Practices - Iyabo, Jegede (2014)
Security to lives and properties in Nigeria at the moment is frustratingly appalling. The situation is so tense that citizens sleep with their eyes open praying for day break as each day passes by. No one is sure of the next victim of bomb blast or criminal attack by hoodlums. The future of the nation looks bleak because of these disturbing problems. The pre-colonial traditional societies were peaceful despite the different Kingdoms that existed irrespective of their cultural and social values and crime control mechanisms were effective, this could be attributed to the strong adherence to social and cultural values in place. Within the Yoruba indigenous communities, hard work which was highly esteemed was inculcated through socialization process and societal norms and values were communicated through indigenous music, myth, folklores and taboos. The parental practices of grooming children to embrace hard work as the key to success are gradually waning if not dead already. No doubt Nigerian governments have made some effort to redress crime and security problems within the society, but are the measures really effective? Hence this paper attempts to provide an appraisal of the Yoruba indigenous traditional social and cultural values as antidote to security and criminal problems in Nigeria. Keywords: Security, Crime, Bomb blast, Indigenous communities, Social value